Case Report: Ambient Sensor Signals as Digital Biomarkers for Early Signs of Heart Failure Decompensation - Saner, Hugo; Schuetz, Narayan; Buluschek, Philipp; Du Pasquier, Guillaume; Ribaudo, Giuseppe; Urwyler, Prabitha; Nef, Tobias (Frontiers in Cardiovascular Medicine, 2021)
Home monitoring systems are increasingly used to monitor seniors in their apartments for detection of emergency situations. More recently, multimodal ambient sensor systems are also used to monitor digital biomarkers to detect clinically relevant health problems over longer time periods. Clinical signs of HF decompensation including increase of heart rate and respiration rate, decreased physical activity , reduced gait speed, increasing toilet use at night and deterioration of sleep quality have a great potential to be detected by non-intrusive contactless ambient sensor systems and negative changes of these parameters may be used to prevent further deterioration and hospitalization for HF decompensation. This is to our knowledge the first report about the potential of an affordable, contactless and unobtrusive ambient sensor system for the detection of early signs of HF decompensation based on data with prospective data acquisition and retrospective correlation of the data with clinical events in a 91 year old senior with a serious heart problem over one year. The ambient sensor system detected an increase of respiration rate, heart rate, toilet use at night, toss and turns in bed and a decrease of physical activity weeks before the decompensation. In view of the rapidly increasing prevalence of HF and the related costs for the health care systems and the societies, the real potential of our approach should be evaluated in larger populations of HF patients.